2014
DOI: 10.1167/14.3.17
|View full text |Cite
|
Sign up to set email alerts
|

Looking against the light: How perception of translucency depends on lighting direction

Abstract: Translucency is an important aspect of material appearance. To some extent, humans are able to estimate translucency in a consistent way across different shapes and lighting conditions, i.e., to exhibit translucency constancy. However, Fleming and Bülthoff (2005) have shown that that there can be large failures of constancy, with lighting direction playing an important role. In this paper, we explore the interaction of shape, illumination, and degree of translucency constancy more deeply by including in our an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(122 citation statements)
references
References 52 publications
6
112
0
Order By: Relevance
“…In recent years, there has been significant progress in developing rendering algorithms and representations that, by modeling the underlying physics, can create realistic reproductions of translucency (Jensen, Marschner, Levoy, & Hanrahan, 2001; Donner & Jensen, 2008; Gkioulekas et al, 2013). As with physics, there have likewise been previous efforts trying to decipher the other major aspect of translucent appearance, namely its perception by the human visual system (Fleming & Bülthoff, 2005; Motoyoshi, 2010; Anderson, 2011; Nagai et al, 2013; Gkioulekas et al, 2013; Xiao et al, 2014; Chowdhury, Marlow, & Kim, 2017; Marlow, Kim, & Anderson, 2017). Despite this, our understanding of translucency perception remains limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been significant progress in developing rendering algorithms and representations that, by modeling the underlying physics, can create realistic reproductions of translucency (Jensen, Marschner, Levoy, & Hanrahan, 2001; Donner & Jensen, 2008; Gkioulekas et al, 2013). As with physics, there have likewise been previous efforts trying to decipher the other major aspect of translucent appearance, namely its perception by the human visual system (Fleming & Bülthoff, 2005; Motoyoshi, 2010; Anderson, 2011; Nagai et al, 2013; Gkioulekas et al, 2013; Xiao et al, 2014; Chowdhury, Marlow, & Kim, 2017; Marlow, Kim, & Anderson, 2017). Despite this, our understanding of translucency perception remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the perception of translucency is confounded by the fact that there exists a tight coupling between how humans perceive the illumination, shape, and material properties of translucent objects (Xiao et al, 2014; Marlow et al, 2017). Recently, Chowdhury et al (Chowdhury et al, 2017) showed that the perception of the 3D shape of a translucent object is different from that of an opaque one.…”
Section: Introductionmentioning
confidence: 99%
“…For example, to grasp a sweater, it is helpful to know its heaviness and stretchability before we come into contact with it. Previous work in material perception has mainly focused on understanding the optical properties of rigid objects, such as the surface gloss and translucency (Fleming, Dror, & Adelson, 2003;Fleming & Bülthoff, 2005;Landy, 2007;Motoyoshi, Nishida, Sharan, & Adelson, 2007;Ho, Landy, & Maloney, 2008;Xiao & Brainard, 2008;Kim & Anderson, 2010;Wijntjes & Pont, 2010;Motoyoshi, 2010;Doerschner et al, 2011;Fleming, Jäkel, & Maloney, 2011;Gkioulekas et al, 2013;Xiao et al, 2014). But many materials around us are soft and deformable (e.g., cloth, gels, and liquids).…”
Section: Introductionmentioning
confidence: 99%
“…A potential reason for this is that a material's surface reflectance properties create some of its most salient optical characteristics and relying on such characteristics could carry ecological importance when other cues to material are not available. For instance, the visual effects of translucency can be greatly diminished with frontal lighting (Xiao et al, 2014); in such cases, image features caused by specular reflections might remain diagnostic of translucent materials (e.g. porcelain).…”
Section: Discussionmentioning
confidence: 99%